Heart valve sclerosis predicts all-cause and cardiovascular mortality - Völzke, Henry; Haring, Robin; Lorbeer, Roberto; Wallaschofski, Henri; Reffelmann, Thorsten; Empen, Klaus; Rettig, Rainer; John, Ulrich; Felix, Stephan B.; Dörr, Marcus (Atherosclerosis, 2010)
Aortic valve sclerosis (AVS) and mitral annulus calcification (MAC) might predict future adverse events. We undertook the present study to investigate the association of AVS and MAC with all-cause and cardiovascular mortality. We further studied whether a combined presence of AVS and MAC is more strongly associated with mortality than the single items and sought to disclose possible gender differences in the investigated associations. We used data from 2081 participants aged ≥45 years (1063 women) of the Study of Health in Pomerania (SHIP). AVS and MAC were determined echocardiographically, and a heart valve sclerosis score was calculated by summing up the AVS and MAC variables. The median duration of mortality follow-up was 8.6 years (17,162 person-years). There were 528 subjects (25.4%) with isolated AVS, 35 with isolated MAC (1.7%) and 89 with both AVS and MAC (4.3%). A total number of 228 deaths (11.0%) occurred during follow-up, including 133 (21.6%) with AVS and 95 subjects (6.5%) without AVS (incidence rate ratio 3.49, 95% CI 2.77; 4.40, p < 0.001). Likewise, mortality rates were higher for subjects with MAC than subjects without MAC (incidence rate ratio 3.79, 95% CI 2.82; 5.02, p < 0.001). Multivariable analyses revealed that the associations of AVS and MAC with all-cause and cardiovascular mortality were independent of major confounders and strongest for highest values of the heart valve sclerosis score. AVS-related mortality was more pronounced in women than in men. AVS and MAC are associated with all-cause and cardiovascular mortality. The association between AVS and mortality is gender-specific with women with AVS being at a higher mortality risk than men with AVS. The summation of AVS and MAC to a heart valve sclerosis score improves the predictability with respect to mortality.